Multicentre Study on the Efficacy of Brachial Artery Transposition Among Haemodialysis Patients. (June 2021) - Murakami, Masaaki; Mori, Kiyoshi; Hamanoue, Satoshi; Suemitsu, Kotaro; Kajiwara, Kengo; Miyamoto, Masahito; Inoue, Hideki; Sueki, Shina; Nihei, Hiroshi; Mukoyama, Masashi
Abstract : Objective: Brachial artery transposition (BAT) is not a well known method for obtaining vascular access (VA) for maintenance haemodialysis. This study evaluated the outcomes of BAT. Methods: This multicentre retrospective cohort study included 233 consecutive patients who underwent BAT between January 2012 and December 2013. The indications were inadequate vessels for obtaining VA, severe heart failure, hand ischaemia, central vein stenosis/occlusion, or a history of catheter/graft infection. The transposed brachial artery was used only for arterial inflow and other routes were used for outflow. Results: BAT was successful in 227 patients, and adequate blood flow was achieved during dialysis sessions. The first successful cannulation was after a median of 18 days. BAT was performed using superficial veins as the return route in 127 patients and arteriovenous fistula (AVF) creation in 63 patients to prevent maturation failure. In 41 patients with central venous catheterisation, the transposed brachial artery was used for arterial inflow. The complications of BAT were impaired wound healing in 14 patients, including skin necrosis in two; large aneurysms in six, including a mycotic pseudo-aneurysm in one; arterial thrombosis in five; hand ischaemia in five; lymphorrhoea in four; and haematoma/bleeding in three. The transposed brachial artery was abandoned in four, three, three, and one case of arterial thrombosis/stenosis, haematoma/bleeding, skin necrosis, and large aneurysm, respectively. Access to the return routes failed in 48 cases because of vein damage caused by cannulation in 22, AVF thrombosis/stenosis in 14, catheter infection in six, and catheter occlusion in six. At two years, the primary patency rates of the transposed brachial artery and access circuit were 88% and 54%, respectively. Conclusion: BAT is a safe and effective technique. The patency was high for the transposed brachial artery but adequate for the access circuit. BAT can be considered for patients with an unobtainable standard arteriovenous access.